The civil society monitoring of hepatitis C response related to the WHO 2030 elimination goals in 35 European countries - M. Maticic; Z. Pirnat; A. Leicht; R. Zimmermann; T. Windelinck; M. Jauffret-Roustide; E. Duffell; T. Tammi; E. Schatz (BMC, 2020)
Abstract Background People who inject drugs (PWID) account for the majority of new cases of hepatitis C virus (HCV) infection in Europe; however, HCV testing, and treatment for PWID remain suboptimal. With the advent of direct acting antivirals (DAAs) the World Health Organization (WHO) adopted a strategy to eliminate HCV as public health threat by 2030. To achieve this, key policies for PWID must be implemented and HCV continuum of care needs to be monitored. This study presents results of the first monitoring led by civil society that provide harm reduction services for PWID. Methods In 2019, harm reduction civil society organizations representing focal points of Correlation-European Harm Reduction Network in 36 European countries were invited to complete a 27-item online survey on four strategic fields: use/impact of guidelines on HCV testing and treatment for PWID, availability/functioning of continuum of care, changes compared to the previous year and, the role of harm reduction services and non-governmental organizations (NGOs) of PWID. A descriptive analysis of the responses was undertaken. Results The response rate was 97.2%. Six countries reported having no guidelines on HCV treatment (17.1%). Twenty-three (65.7%) reported having treatment guidelines with specific measures for PWID; guidelines that impact on accessibility to HCV testing/treatment and improve access to harm reduction services in 95.6% and 86.3% of them, respectively. DAAs were available in 97.1% of countries; in 26.4% of them they were contraindicated for active drug users. HCV screening/confirmatory tests performed at harm reduction services/community centers, prisons and drug dependence clinics were reported from 80.0%/25.7%, 60.0%/48.6%, and 62.9%/34.3% of countries, respectively. Provision of DAAs at drug dependence clinics and prisons was reported from 34.3 to 42.9% of countries, respectively. Compared to the previous year, HCV awareness campaigns, testing and treatment on service providers' own locations were reported to increase in 42.9%, 51.4% and 42.9% of countries, respectively. NGOs of PWID conducted awareness campaigns on HCV interventions in 68.9% of countries, and 25.7% of countries had no such support. Conclusion Further improvements in continuum-of-care interventions for PWID are needed, which could be achieved by including harm reduction and PWID organizations in strategic planning of testing and treatment and in efforts to monitor progress toward WHO 2030 elimination goal.